2001
DOI: 10.1136/thorax.56.5.379
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary infiltrates in non-HIV immunocompromised patients: a diagnostic approach using non-invasive and bronchoscopic procedures

Abstract: Background-The development of pulmonary infiltrates is a frequent life threatening complication in immunocompromised patients, requiring early diagnosis and specific treatment. In the present study non-invasive and bronchoscopic diagnostic techniques were applied in patients with diVerent non-HIV immunocompromised conditions to determine the aetiology of the pulmonary infiltrates and to evaluate the impact of these methods on therapeutic decisions and outcome in this population. , 10%), and the most frequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
4
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(113 citation statements)
references
References 27 publications
8
95
4
6
Order By: Relevance
“…When reported, FOB typically occurred 4 or more days following the initiation of empiric antibiotics. 11,12,25,27,28 Thus, our findings corroborate previous observations that link diagnostic delays to poor patient outcome and underscore the futility of late FOBguided antimicrobial adjustments in offsetting mortality among HSCT recipients with suspected pneumonia. A notable difference in our study compared with previousreports, however, is the significantly lower mortality rate associated with antibiotic modifications following early FOB.…”
Section: Discussionsupporting
confidence: 81%
“…When reported, FOB typically occurred 4 or more days following the initiation of empiric antibiotics. 11,12,25,27,28 Thus, our findings corroborate previous observations that link diagnostic delays to poor patient outcome and underscore the futility of late FOBguided antimicrobial adjustments in offsetting mortality among HSCT recipients with suspected pneumonia. A notable difference in our study compared with previousreports, however, is the significantly lower mortality rate associated with antibiotic modifications following early FOB.…”
Section: Discussionsupporting
confidence: 81%
“…In these patients, reported diagnostic yields range from 35 to 60%. 8,9,11,12,15,17,[18][19][20][21][22][23][24] We found comparable results in our patients with lymphoid malignancies, with a diagnostic yield of 50%. The much lower diagnostic yield of FOB-BAL in our AML patients with ARF admitted in ICU raises several issues, dominated by the differences in studied populations between available reports.…”
Section: Overall Diagnostic Yield Of Fob-balsupporting
confidence: 72%
“…In our review, 20% of ventilated patients lived more than 60 days from bronchoscopy in comparison to 43% in non-intubated patientsthis supports other published reports that only autograft recipients intubated for uncomplicated lung injury 24 and allograft recipients intubated at the time of engraftment 25 should be expected to survive to hospital discharge. Rano et al 23 showed that a delay greater than 5 days in the identification of the cause of the pulmonary infiltrates increased the risk of death threefold, but we found that survival was not statistically different after a diagnostic or non-diagnostic bronchoscopy; this difference may be accounted for by our focus on only HSCT patients. This suggests that other variables such as the extent or severity of graft-versus-host disease (GVHD), the forced expiratory volume in 1 s to forced vital capacity ratio, or cumulative steroid treatment may better predict patients more likely to die from an opportunistic pulmonary infection.…”
Section: Discussioncontrasting
confidence: 44%
“…In the largest study of bronchoscopy in non-human immunodeficiency virus immunocompromised patients with pulmonary infiltrates, Rano et al 23 (27% HSCT recipients) described three variables that predicted mortality: increasing severity of illness, need for mechanical ventilation and delay in diagnosis. In our review, 20% of ventilated patients lived more than 60 days from bronchoscopy in comparison to 43% in non-intubated patientsthis supports other published reports that only autograft recipients intubated for uncomplicated lung injury 24 and allograft recipients intubated at the time of engraftment 25 should be expected to survive to hospital discharge.…”
Section: Discussionmentioning
confidence: 99%